PERAN KEPALA SEKOLAH SEBAGAI SUPERVISOR DALAM MENINGKATKAN DISIPLIN KERJA GURU DI SMP NEGERI 45 MEDAN TAHUN AJARAN 2019/2020 - Sangkot Basuki (Universitas Islam Negeri Sumatera Utara Medan, 2022)
The purpose of this school action research is to determine teacher performance and the role of the principal as a supervisor in improving teacher work discipline at SMP Negeri 45 Medan. The research method is descriptive analysis, the sample is 25 teachers at SMP Negeri 45 Medan, Labuhan District. Data collection techniques using questionnaires, observation and interviews. Based on the results of the study, it can be concluded that from the percentage data above, a conclusion can be drawn that the role of the school principal as a supervisor in improving work discipline is in the very effective category. The aspect of the school principal as a supervisor with a percentage value of 82.35% and the percentage of teacher work discipline is 69.5%. This shows that the role of the principal as a supervisor is very effective with an average overall percentage score of 78.68%, this means that supervision activities are very important to be carried out related to personal and professional improvement for teachers to be more disciplined. The researcher suggests holding training and knowledge of the duties and responsibilities of the teaching profession so that it is hoped that it will increase teacher awareness to prioritize work discipline behavior.